Compiling a 50-year journey*. (20th September 2017) - HUTTON, GRAHAM; BAHR, PATRICK
Abstract: Fifty years ago, John McCarthy and James Painter (1967) published the first paper on compiler verification, in which they showed how to formally prove the correctness of a compiler that translates arithmetic expressions into code for a register-based machine. In this article, we revisit this example in a modern context, and show how such a compiler can now be calculated directly from a specification of its correctness using simple equational reasoning techniques.